Production of poly (ε-caprolactone) Antimicrobial Nanofibers by Needleless Alternating Current Electrospinning. (2019) - Manikandan, S.; Divyabharathi, M.; Tomas, K.; Pavel, P.; David, L.
Abstract: The present study is focused on the fabrication of antimicrobial polycaprolactone (PCL) nanofibers using uncommon needleless and collector less alternating current (AC) electrospinning. The PCL polymeric solutions (6 & 12 wt.%) were prepared using 1:1 acetic acid and formic acid. The antimicrobial agent chlorhexidine (CHX) was added to the PCL precursor solution at 1 wt%. The PCL/CHX solutions (6 &12 wt.%) were electrospinnable at the applied AC potential of 25kV and 35kV rms. The surface morphological investigation of PCL/CHX antimicrobial nanofibers confirmed that smooth beadless nanofibers have been obtained. Fiber diameter and viscosity were increasing with respect to PCL/CHX concentrations.